EFFICIENT AND GUARANTEED QUALITY OF SERVICE (QOS) ROUTING ALGORITHM FOR VEHICULAR NETWORKS (VANETS) - AMINU MUAZU, ABUBAKAR (2014)
The vehicular ad hoc network (VANET) is a technology that provides mobile vehicles with endless possibilities of applications, including safety messaging exchange, real-time traffic information sharing and route condition updates etc. This network is characterized by rapid topology changes due to the high displacement of vehicles making Quality of Service (QoS) provisioning a challenging task especially for real-time and multimedia applications. Providing priority to certain traffic types has been widely used in V ANET for selecting a stable route with QoS constraints. This brings along another challenging task in V ANET environment. In an effort to provide QoS in VANET, the IEEE 802.1lp physical layer (regarded as VANET MAC protocol) experiences a huge amount of packet loss rate as a result of data collisions. Somehow its performance can be improved by using Time Division Multiple Access (TDMA) techniques.